Translating Libyan and Arabic Proverbs: Across-Cultural Study on Linguistic and Cultural Challenges in Arabic Translation into English (Elmergib Journal of Human Sciences, 2024)
proverbs are a widely spread phenomenon. Translating proverbs necessitates more than just direct word-for-word substitution. It requires understanding the underlying message, symbolism, cultural references and context of the proverb in order to convey its intended meaning in the target language. This paper sheds light on translating Arabic and Libyan proverbs by the seventh semester students at the Department of English in Tripoli University . It starts with introducing the definitions of translation, culture and proverbs. Then, it presents a translation test to Know how students translate proverbs within texts and to identify the problems they face in this respect. Finally, it summarizes the findings of the test which show that the students at the Department of English encounter some difficulties in translating  Arabic and Libyan proverbs into English. These difficulties include the insufficient knowledge about both cultures and the use of improper translation techniques and strategies were key factors contributed to the unsuccessful translation.